Using mathematical model to design and sizing of pumping water system - Luqman Raji; Y Gajawa; Aji A. B.; Kasni Sumeru (Jurnal Internasional Penelitian Teknologi Terapan, 2022)
The role of the pump in any pumping system is to provide sufficient pressure to overcome the operating pressure of the system in order to move fluid (water) at a required flow rate to the user. In this study, a mathematics model was used for design in order to provide adequate water supply to every quarter in Federal Polytechnic Mubi, Adamawa state Nigeria. According to the research, the proposed water supply requires a 1360W power pump, a 1500W inverter, and a 1500W solar panel. Because the suggested water supply is based on renewable energy, the study found that it can be used at Federal Polytechnic Mubi to increase their supply for human use. As a result, the FPM management has reduced greenhouse gas emissions.